1996
DOI: 10.1007/bf01245968
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and ecology of Old World Luperini beetles of the genusAulacophora (Coleoptera: Chrysomelidae)

Abstract: Summary. The attraction of Old World leaf beetles in the genus AuIacophora to kairomones and parakairomones which are effective lures for New World Diabrotica and Acalymma were investigated. Beetles captured on sticky traps baited with single and multicomponent lures were no different from the control traps for two species of Aulacophora. Yellow colored traps and squash blossoms are attractive to Aulacophora beetles which detect sub-microgram quantities of cucurbitacins on silica gel. Leaf feeding behavior and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…These defense metabolites are oxygenated tetracyclic triterpenes that are extremely bitter and render plants toxic or unpalatable to many invertebrates and vertebrate herbivores, including humans (Da Costa and Jones, 1971 , Ferguson and Metcalf, 1985 ). However, cucurbitacins can also serve as kairomones (semiochemicals that benefit certain receivers) (Metcalf, 1986 ) for a number of specialized phytophagous chrysomelid beetles of the Old World tribe Luperini, in the genus Aulacophor a (Jaccard et al, 2021 , Chambliss and Jones, 1966 , Castellanos‐Morales et al, 2018 , Lewis and Metcalf, 1996 ). Both squash and Diabroticine beetles share origins in Mesoamerica and have coevolved over an extended period of time (Metcalf, 1979 , Metcalf, 1986 , Metcalf and Lampman, 1989 ).…”
Section: Introductionmentioning
confidence: 99%
“…These defense metabolites are oxygenated tetracyclic triterpenes that are extremely bitter and render plants toxic or unpalatable to many invertebrates and vertebrate herbivores, including humans (Da Costa and Jones, 1971 , Ferguson and Metcalf, 1985 ). However, cucurbitacins can also serve as kairomones (semiochemicals that benefit certain receivers) (Metcalf, 1986 ) for a number of specialized phytophagous chrysomelid beetles of the Old World tribe Luperini, in the genus Aulacophor a (Jaccard et al, 2021 , Chambliss and Jones, 1966 , Castellanos‐Morales et al, 2018 , Lewis and Metcalf, 1996 ). Both squash and Diabroticine beetles share origins in Mesoamerica and have coevolved over an extended period of time (Metcalf, 1979 , Metcalf, 1986 , Metcalf and Lampman, 1989 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the feeding response of Aulacophora beetle species to cucurbitacins revealed the feeding stimulant activity of cucurbitacins: A. foveicollis was stimulated to feed by cucurbitacin E Krishna, 1969, 1970), A. lewisii and A. coffeae strongly responded to cucurbitacin D (Lewis and Metcalf, 1996), A. indica and A. lewisii were stimulated to feed by cucurbitacins B, E, I, and E-glucoside . However, the feeding preference of Aulacophora beetle species to the other cucurbitacins is unknown as yet.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, A. lewisii was strongly stimulated to feed by the cucurbitacins, but the beetle feeds almost solely on leaves from the genus Luffa (Lewis and Metcalf, 1996;. For these reasons, we have come to believe that some other constituents in addition to the cucurbitacins in leaves of cucurbitaceous plants play important roles in the host plant selection by the Aulacophora beetles.…”
Section: Introductionmentioning
confidence: 95%
“…However, it feeds and grows rapidly beyond trenches cut by cabbage loopers (Dussourd, 1993; Dussourd & Denno, 1994). Fifth, some insects show vein cutting and trenching behaviour facultatively; the insects do not employ canal cutting on plants lacking exudates or with low levels of exudates (Dussourd & Denno, 1994; McCloud, Tallamy & Halaweish, 1995; Lewis & Metcalf, 1996; Evans et al. , 2000).…”
Section: Introductionmentioning
confidence: 99%